ILMU DAN ORANG BERILMU DALAM AL-QUR’AN: MAKNA ETIMOLOGIS, KLASIFIKASI, DAN TAFSIRNYA - Ferry Muhammad Siregar, Surahman Amin dan (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2015)
This paper aims at discussing about knowledge (‘al-‘ilm) and scholar (al-‘ālim) in the Qur’an with a focus on their etymological meanings, classification and interpretation (tafsīr). In addition, it examines the words of verses related to al-‘ilm and al-ālim, being analyzed by the theory of Qur’anic exegesis, especially tafsīr mauḍū’ī. It faund that the al-‘ilm is a real knowledge on an object in accordance with its conditions and characters. Al- ’ilm can be divided into two types, i.e. kasbī (gained knowledge) and ladunnī or mawhibah (gifted knowledge).Keywords: Knowledge, Tafsīr, ‘Ulamā’